First report of a sleeper shark (Somniosus sp.) in the southern Colombian Caribbean. (4th May 2018) - Acero P, Arturo; Polo‐Silva, Carlos J.; León, Jorge; Puentes, Vladimir
Summary: A sleeper shark, genus Somniosus, was observed in the Colombian Caribbean. A Remote Operated Vehicle (ROV) recorded a sleeper shark specimen during an inspection while drilling a hydrocarbon exploratory well at 1, 820 m water depth. This is the first record of a sleeper shark for the southern Colombian Caribbean. The previous most southern records of Somniosid sharks in the tropical and subtropical western Atlantic came from the western and northern Gulf of Mexico, and from Cuba.